2008
DOI: 10.1080/10428190801911654
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine kinase 1 protein and mRNA are overexpressed in non-Hodgkin lymphomas and are attractive targets for novel pharmacological interventions

Abstract: Sphingosine kinase 1 (SphK1) is an oncoprotein capable of directly transforming cells and is associated with resistance to chemotherapy and radiotherapy. SphK1 is increased in various human cancers; whereas, blockade restores sensitivity to therapeutic killing in chemotherapy resistant cancer cell lines. We investigated SphK1 expression in clinical tissue samples from patients with non-Hodgkin lymphomas (NHL). Tissues from 69 patients with either NHL (n = 44) or reactive lymphoid hyperplasias (RH) (n = 25) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(40 citation statements)
references
References 16 publications
4
36
0
Order By: Relevance
“…Sphingosine kinase 1 expression was significantly increased in thyroid cancer tissues compared to nodular goiter (p<0.001) and normal thyroid (p<0.001) tissues, consistent with previous results (14,16,20,(32)(33)(34). We observed that 34 (30.9%) of 110 papillary thyroid carcinoma tissue samples had high sphingosine kinase 1 expression.…”
Section: Discussionsupporting
confidence: 80%
“…Sphingosine kinase 1 expression was significantly increased in thyroid cancer tissues compared to nodular goiter (p<0.001) and normal thyroid (p<0.001) tissues, consistent with previous results (14,16,20,(32)(33)(34). We observed that 34 (30.9%) of 110 papillary thyroid carcinoma tissue samples had high sphingosine kinase 1 expression.…”
Section: Discussionsupporting
confidence: 80%
“…In addition to cancer cells, tumors contain a repertoire of recruited ostensibly normal cells that contribute to cancer biology by creating the tumor microenvironment. Cancer cells do not manifest the disease alone, but rather conscript and corrupt resident and recruited normal cells, and collaborative ( 31 ), colon ( 34,35 ), breast ( 36,37 ), prostate ( 38 ), nonHodgkin's lymphoma ( 39 ), chronic myeloid leukemia ( 40 ), astrocytoma ( 41 ), and glioblastoma ( 42 ). In several of these studies, increased SphK1 expression correlated with increased tumor grade and poor prognosis.…”
Section: S1p and Its Roles In Cancermentioning
confidence: 99%
“…Elevated expression of SphK1 is associated with numerous cancer types Sobue et al, 2008;Paugh et al, 2009;Knapp et al, 2010;Malavaud et al, 2010;Guan et al, 2011), and several lines of evidence link SphK1 deregulation with the progression of various hematologic malignancies (Van Brocklyn et al, 2005;Bonhoure et al, 2006;Bayerl et al, 2008;Paugh et al, 2008;Pitson et al, 2011). For example, overexpression of SphK1 has been shown to be an oncogenic event in acute erythroid leukemia progression (Le Scolan et al, 2005).…”
Section: Introductionmentioning
confidence: 99%